La profesionalización de docentes interculturales bilingües y su incidencia en el ámbito educativo :Estudio del caso en las parroquias San Francisco, Sagrario, Imantag y Quiroga del cantón Cotacachi, provincia de Imbabura - Alta Cabezas, María Alexandra (2015)
This work degree is the result of a space for dialogue with different actors of the Salesian Polytechnic University ( UPS ) and ten teachers who have graduated Career Intercultural Bilingual Education of the same university, where the professionalization of analyzes Intercultural Bilingual teachers and their impact on education. Within this research presented in the first part intercultural bilingual education (EIB ) in Ecuador through history, constitutional foundations that support the EIB in Ecuador and a brief description of EIB experiences in seven countries in Latin America, and the major issues and challenges of it. In the second chapter we have the historical background of the School of Intercultural Bilingual Education UPS , goals, objectives and curriculum of the race, description of the five support centers Ecuador level , especially Otavalo Support Center . The third chapter is the collection of data on different cohorts of students who have graduated Support Center Otavalo, a description of the parishes San Francisco, Sagrario , Imantag and Quiroga of Cotacachi and analysis of interviews and surveys of managers , parents , students and IB teachers, finally we have successes and difficulties of the same in education .